The Appearance of the Scitovsky Paradox in the Coase Theorem - Barancsuk, János (Marketing & Menedzsment, 2019)
AIMS OF THE PAPER Our study aims to interpret the Coase theorem in a way which also allows us to interpret the basic doctrine within the logical space of the Kaldor-Hicks-Scitovsky tests. In doing this we try to prove that, in the case of stakeholders with conflicting interests in using the environment (the so-called “environmental conflict”) the relevance of the Coase theorem may be questioned by the Welfare test recommended by Scitovsky. Our further aim is to define those limiting conditions under which the conflict amongst stakeholders may still be able to produce Pareto’s efficient allocation of resources. METHODOLOGY Our research is based on the recognition that Coase’s recommendation to compensate the welfare losses generated by external effects, can be checked by the Kaldor, Hicks and s Scitovsky tests. After showing the isomorphism latent in both concepts, we concentrate on how the options of compensation between actors A and B are formulated if the law regulating the use of the common environment (compared to the earlier version) shows the person who must bear the burden as different from the one who has the benefit. In respect of our research aims, we considered comparative statistical analysis as being the most appropriate. MOST IMPORTANT RESULTS We have explored further conditions or limitations relating to the socially tolerable or desirable value of the externalities (both burdens and benefits), and, in general theoretical terms, the optimal distribution of resources. Our results ultimately support those views which give rise to (at least some) doubts regarding the general interpretability of Pareto’s efficient allocation of production factors, or the Pareto Improvement. Our research has also shed light on the fact that, under an extreme ratio of resource distribution (in respect of the division of externalities close to 50:50), the chances of achieving the Pareto optimal improve, whilst otherwise they worsen. RECOMMENDATIONS Our results suggest that we need to have some reservations in respect of the theory and practice of the “market-conform” treatment of external economic impacts. We further conclude that, in the economic space burdened with external impacts, more consideration should be given to structural regulation which is more tolerant of the concentrated spread of inputs, in case we should face an “all or nothing” situation in terns of the comfortable use of the environment.